2002
DOI: 10.1136/oem.59.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air pollution and environmental tobacco smoke on serum hyaluronate concentrations in school children

Abstract: Objectives: To evaluate serum hyaluronate concentrations relative to air pollution, environmental tobacco smoke (ETS), and respiratory health in Japanese school children. Methods: Respiratory symptoms and serum IgE concentrations were examined in 1037 school children living in four communities in Japan with differing levels of air pollution. Serum hyaluronate concentrations were assayed in 230 children, consisting of all the children who had symptoms of either asthma or wheeze (65 and 50 subjects, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In contrast to the protective role of HA in lung physiology, it has also been reported that: serum levels of HA did not differ between patients with asthma or wheeze compared with normal controls [37]; inhaled low molecular mass HA (0.15610 6 kDa) did not significantly protect against exerciseinduced bronchoconstriction in asthmatic patients [38]; and there are increased levels of HA in lung secretions of asthma [39] and COPD [13] patients. However, these apparently contradictory reports may be explained as follows: 1) HA serum levels may not necessarily reflect HA levels in the lung; 2) it is the high molecular mass HA that exerts beneficiary effects; 3) lower molecular mass HA (0.3-0.5610 6 kDa) predominate under inflammatory conditions [14]; 4) the increased levels of HA in lung secretions of asthma and COPD patients may reflect enhanced degradation and subsequent secreation of HA, as a consequence of the increased expression of Hyal2 in COPD patients [13] and Hyal1 in ASMC that we report here.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to the protective role of HA in lung physiology, it has also been reported that: serum levels of HA did not differ between patients with asthma or wheeze compared with normal controls [37]; inhaled low molecular mass HA (0.15610 6 kDa) did not significantly protect against exerciseinduced bronchoconstriction in asthmatic patients [38]; and there are increased levels of HA in lung secretions of asthma [39] and COPD [13] patients. However, these apparently contradictory reports may be explained as follows: 1) HA serum levels may not necessarily reflect HA levels in the lung; 2) it is the high molecular mass HA that exerts beneficiary effects; 3) lower molecular mass HA (0.3-0.5610 6 kDa) predominate under inflammatory conditions [14]; 4) the increased levels of HA in lung secretions of asthma and COPD patients may reflect enhanced degradation and subsequent secreation of HA, as a consequence of the increased expression of Hyal2 in COPD patients [13] and Hyal1 in ASMC that we report here.…”
Section: Discussionmentioning
confidence: 91%
“…However, the molecular size of this HA was not measured 27 . School children living in communities with high levels of pollution have increased serum levels of HA, but again the size has not been measured 28 . Cigarette smoke has been shown to degrade HA and to decrease the chain length in vitro , suggesting that cigarette smoke may degrade HMW HA to pro‐inflammatory LMW HA 29 .…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] There has long been a need for sensitive biomarkers to objectively evaluate the chronic effects of air pollution on human health as early as possible, but none has yet been identified. 5,6 Previously, we reported an association between serum concentrations of acute phase proteins or hyaluronate in children and concentrations of air pollutants, 7,8 but assays for these serum factors have not been validated as biomarkers for the effects of air pollution. C-reactive protein (CRP) in serum has been widely used as a marker for infectious disease.…”
mentioning
confidence: 99%